Evaluation of furrow irrigation practices in Fergana Valley of Uzbekistan - Reddy, Junna Mohan; Jumaboev, Kahramon; Matyakubov, Bakhtiyar; Eshmuratov, Davron (Elsevier, 2013)
The performance of furrow irrigation systems in terms of application efficiency, runoff ratio, and water requirement efficiency were evaluated at nine different sites within the Provinces of Fergana (6 sites) and Andijon (3 sites) in Uzbekistan. A total of 46 irrigation events were evaluated during the year 2009, whereas only a total of 8 irrigation events (at 3 sites) were evaluated during the year 2010. Most of the selected fields have slopes greater than 0.005; hence, the average runoff volume from these fields was 39% of the total volume of water applied to the fields, indicating problems with selection of appropriate furrow flow rates under the given set of field conditions. For several fields, the seasonal volume of water applied was significantly different than the irrigation norms specified for the site. Though some of the farmers followed the irrigation advisory service on when to irrigate, there was a large mismatch between the volume of water applied and the volume of water deficit within the crop root zone. Reliability, in terms of magnitude and duration of flow rate received at the fields, was a major issue at all the sites. Considerable fluctuations were observed in the flow rates received at all the field sites during each irrigation event. In addition, the average flow rate received at the field sites varied considerably between irrigation events making it difficult for farmers to manage irrigation water. Farmers that had high watertable (less than 100 cm from the ground surface) still applied large volumes of water, resulting in low application efficiency. Several recommendations for improving the performance of furrow irrigation systems in Uzbekistan are provided.